2020
DOI: 10.1177/0363546520980079
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Strength Symmetry Does Not Modify Gait Mechanics After Anterior Cruciate Ligament Reconstruction, Rehabilitation, and Return-to-Sport Training

Abstract: Background: After anterior cruciate ligament (ACL) reconstruction (ACLR), biomechanical asymmetries during gait are highly prevalent, persistent, and linked to posttraumatic knee osteoarthritis. Quadriceps strength is an important clinical measure associated with preoperative gait asymmetries and postoperative function and is a primary criterion for return-to-sport clearance. Evidence relating symmetry in quadriceps strength with gait biomechanics is limited to preoperative and early rehabilitation time points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 59 publications
(82 reference statements)
0
35
0
Order By: Relevance
“…1,15,43 Although this threshold of symmetry appears difficult to reach, previous research has demonstrated that it is possible. 2,46 While it cannot be said with certainty that achieving quadri.tif strength symmetry of >90% will reduce reinjury risk, the current reinjury rates dictate further exploration into the implications of achieving this metric.…”
Section: Discussionmentioning
confidence: 99%
“…1,15,43 Although this threshold of symmetry appears difficult to reach, previous research has demonstrated that it is possible. 2,46 While it cannot be said with certainty that achieving quadri.tif strength symmetry of >90% will reduce reinjury risk, the current reinjury rates dictate further exploration into the implications of achieving this metric.…”
Section: Discussionmentioning
confidence: 99%
“…69 A preoperative focus on quadriceps strength or neuromuscular perturbation response does not appear to significantly improve gait biomechanics after ACLR when compared to protocols without prehab. 70,71 Meanwhile, Giesche et al 72 and Failla et al 73 reported improved functional scores and return-tosport rates in prehab patients at 2-year follow-up. These results suggest that although prehab may not significantly alter postoperative biomechanics, it may provide improvements in outcomes that are more clinically relevant for the patients.…”
Section: Rehabilitation Recommendations the Role Of Prehabilitationmentioning
confidence: 99%
“…However, balance and technique training may not be effective in changing an athlete’s knee joint kinematics or decreasing external knee moments during pre-planned and unplanned side-stepping [ 75 ]. Similarly, gait mechanics are also difficult to modify even after completion of rehabilitation training and restoration of muscle strength [ 76 ]. This may be because the systems have achieved a domain of stability and the parts of the systems are well-entrenched, making it very difficult or near impossible to change.…”
Section: What Is a Complex Systems Approach?mentioning
confidence: 99%